Diagnostic efficacy of sonographic measurement of laryngeal air column width difference for predicting the risk of post-extubation stridor: A meta-analysis of observational studies - Tsai, Wen-Wen; Hung, Kuo-Chuan; Huang, Yen-Ta; Yu, Chia-Hung; Lin, Chien-Hung; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Medicine, 2023)
Background: This meta-analysis aimed at assessing the diagnostic accuracy of ultrasound-measured laryngeal air column width difference (ACWD) in predicting post-extubation stridor (PES) in intubated adult patients. Methods: We searched the Medline, Cochrane Library, EMBASE, and Google scholar databases from inception to October, 2022 to identify studies that examined the diagnostic accuracy of ACWD for PES. The primary outcome was the diagnostic performance by calculating the pooled sensitivity, specificity, and area under the curve (AUC). The secondary outcomes were the differences in ACWD and duration of intubation between patients with and without PES. Results: Following literature search, 11 prospective studies (intensive care setting, n=10; operating room setting, n=1) involving 1322 extubations were included. The incidence of PES among the studies was 4–25%. All studies were mixed-gender (females: 24.1–68.5%) with sample sizes ranging between 41 and 432. The cut-off values of ACWD for prediction of PES varied from 0.45 mm to 1.6 mm.The pooled sensitivity and specificity of ACWD for PES were 0.8 (95% CI = 0.69–0.88, I2: 37.26%, eight studies) and 0.81 (95% CI = 0.72–0.88, I2: 89.51%, eight studies), respectively. The pooled AUC was 0.87 (95% CI = 0.84–0.90). Patients with PES had a smaller ACWD compared to those without PES (mean difference = -0.54, 95% CI = -0.79 to -0.28, I2: 97%, eight studies). Moreover, patients with PES had a longer duration of tracheal intubation than that in those without (mean difference = 2.75 days, 95% CI = 0.92, 4.57, I2: 90%, seven studies). Conclusions: Ultrasound-measured laryngeal air column width difference showed satisfactory sensitivity and specificity for predicting post-extubation stridor. Because of the limited number of studies available, further investigations are needed to support our findings.